Attitude and willingness of local communities toward conservation of urban forest in Selangor - Syed Basir, Syarifah Amirah (2018)
The study was done within Ayer Hitam Forest Reserve (AHFR) and Bangi Forest Reserve (BFR). The study focused on attitude and willingness of local communities toward conservation of urban forest. The main objective of the study was to investigate the attitude and willingness of local communities toward conservation of urban forest and to examine the correlation between local communities’ attitude and willingness to conserve the urban forest. The study used questionnaires survey which distributed randomly to local communities that live within 3 Kilometer from the border of AHFR and BFR. A sample size of 200 respondents was chosen with 100 respondents for each forest. From the findings of the study, it can be concluded that the local community in both study areas generally has positive attitudes towards conservation of urban forest. The local community is positively motivated towards conservation as the majority of the respondents were willing to conserve the urban forest. There was a significant monotonic correlation between the attitude of the local community towards conservation and their willingness to conserve urban forest (rs (198) = .403, p = 0.000). Overall, the attitude and willingness of local communities toward conservation of urban forest in Selangor were positive. Further studies should be done in other urban forests in Selangor by the similar methodology used in this study. It is recommended that conservation education programs should be implemented in order to keep local communities interested in conserving urban forests.